2017
DOI: 10.5812/bhs.57652
|View full text |Cite
|
Sign up to set email alerts
|

Stress Induction and Visual Working Memory Performance: The Effects of Emotional and Non-Emotional Stimuli

Abstract: Background: Some studies have shown working memory impairment following stressful situations. Also, researchers have found that working memory performance depends on many different factors such as emotional load of stimuli and gender.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
7
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 47 publications
(53 reference statements)
1
7
0
Order By: Relevance
“…However, accuracy and RT indices were found to be worsening for negative words in the experimental condition. As regards negative words, our findings are in line with Moran's (2016) and Khayyer et al. (2017) studies that demonstrated that increased stress and anxiety are associated with weaker WM performance (emotional impairment hypothesis).…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…However, accuracy and RT indices were found to be worsening for negative words in the experimental condition. As regards negative words, our findings are in line with Moran's (2016) and Khayyer et al. (2017) studies that demonstrated that increased stress and anxiety are associated with weaker WM performance (emotional impairment hypothesis).…”
Section: Discussionsupporting
confidence: 92%
“…Some studies have also reported that stress can increase memory performance ( Cahill et al., 2003 ; Smeets et al., 2008 ; Lukasik et al., 2019 ). However, other studies have shown that stress can impair memory performance ( Buchanan and Tranel, 2008 ; Colman, 2015 ; Khayyer et al., 2017 ).…”
Section: Introductionmentioning
confidence: 95%
“…Previous studies have indicated that stress causes depression, anxiety, and mood disorders [ 35 ]. Also, stress harms cognitive functions by increasing the secretion of glucocorticoids that activate the hypothalamus-pituitary-adrenal axis [ 26 ].…”
Section: Discussionmentioning
confidence: 99%
“…This can be explained by the fact that the attention system in anxious people has bias towards negative stimuli, in a way that these people are more sensitive to stressful and threatening stimuli. Furthermore, the perceived stress threshold in women is lower than that of men, while women's limbic system is more active, which enables them to experience higher levels of cortisol in stressful situations (Khayyer, Nejati, & Fathabadi, ).…”
Section: Discussionmentioning
confidence: 99%